Crop productivity and nutrient uptake of fenugreek (Trigonella foenum-graecum L.) as influenced by integrated nutrient management (SAARC Journal of Agriculture, 2016)
A field experiment was carried out at Spices Research Centre, Shibgonj, Bogra during two consecutive years, 2013-2014 and 2014-2015 to evaluate the response of integrated nutrient management on nutrient uptake, protein content and seed yield of fenugreek (Trigonella foenum-graecum L.) var. BARI Fenugreek-2. The field experiment was conducted in combination with inorganic fertilizer and organic manure. The result showed that the treatment T7 compeises application of PM @ 4 t ha-1 + CF (IPNS) produced the maximum seed yield (2.1 t ha-1) but statistically identical to T8 (VC @ 3 t ha-1 + CF (IPNS) and T6 (CD 5 @ ha-1 + CF (IPNS). In case of stover yield, the treatment T7 produced the highest yield (4.89 t ha-1). The grain yield was increased over control and ranged between 65.85 to 156.10 %.The treatments T7 and T8 resulted in higher nutrient use efficiency along with higher N, P, K and S uptake by the plant. The application of inorganic fertilizer along with manure influenced the nutrient concentration in fenugreek seed and stover yield. The higher seed with N, P, K and S concentrations were observed in the treatments where poultry manure @ 4 t ha-1 applied in combination with chemical fertilizers. The combined application of fertilizer and organic manure increased the organic carbon (OC %), organic matter (OM %), total N, available P and available S in post harvest soils. The findings indicate that the integrated use of inorganic fertilizer and organic manure should be encouraged to improvement the deteriorating soil fertility and increased crop yield of fenugreek.SAARC J. Agri., 14(1): 71-79 (2016)